Characteristics, origins, and age of the water from Springs and wells on Monte Vulture (Basilicata Region, Italy) - Fuganti, Andrea; Sigillito, Vincenzo (Italian journal of engineering geology and environment, 2008)
Monte Vulture is an extinct Quaternary volcano in Potenza Province (Basilicata Region), in southern Italy. The area is tectonically active, testified by earthquakes. The volcano consists prevalently of tuffs with subordinate lavas, overlying an impermeable Flysch formation. It has abundant groundwater with springs and aquifers containing water with low to high mineralization and in some cases sparkling water. The most common gas is carbon dioxide. Studies were carried out on the water of 24 springs and 21 wells of depths down to 250 metres on the southern central part of the volcano. The chemical parameters of the water sources vary significantly. The variations are dependent on the altitude of the springs, depth of the wells, presence of carbon dioxide, presence of Flysch at the base, the oxic and anoxic conditions, and proximity to faults. The well water temperatures range from 14 to 21.7°C. The caffeine content was studied in the water of 10 wells, 5 springs, and the Fosso Fontanelle river, which rises at Rionero. Caffeine was found only in the water of Fosso Fontanelle. The groundwater is free of caffeine, indicating a high degree of purity. The following isotopic analyses were conducted on the water of 6 deep wells: oxygen 18, deuterium, deuterium excess, krypton-85, tritium, carbon 13 in DIC, carbon 14 in DIC, carbon 13 in the carbon dioxide, the ratio between helium 3 and helium 4, and the ratio between argon 40 and argon 36. The groundwater has 3 components, depending on age. The most recent component is the water in the upper part of the aquifer; the age varying between contemporary to a few decades. This is supplied by local recharge. The second component is water dated from a few decades to a few hundred years. This underlies the water of recent origin and the supply basin is the mid section of the mountain slope. The third component is the deep water with the recharge area on the upper part of Monte Vulture. This component has an age of a few thousand years. The principal form of circulation is the piston flow model.